SOCIO-ECONOMIC IMPACT OF SEXING OF SEMEN - J, ARUNPANDIAN; N, SRIVASTAVA; M, GANESAN; KUJUR, ANJU; V, GOWTHAMAN (The Indian Journal of Animal Reproduction, 2021)
Nowadays sexing of semen is slowly developing among dairy producers and farmers and benefit both thefarmers and industry. Sexing of semen is used to sort out the healthy as well as more specific traits in which spermatozoaare separated into X-bearing or Y-bearing chromosome populations through either selection or sorting. The sexsortedsemen is collected from genetically superior animals so the result of milk production and quality of meat will getup to the expected level. The use of sex-sorted semen mainly produced the female heifer in dairy farms or herdswhich reduced the purchasing number and price of cattle from outside. Collectively, the rate of genetic change hasbeen expected to increase by not more than 15% as a result of the increased selection of dams through sexedsemen.
Keywords: Sexed semen; India; Breeding technique; X-chromosome; Female calf